2007
DOI: 10.1084/jem.20070885
|View full text |Cite
|
Sign up to set email alerts
|

The healing myocardium sequentially mobilizes two monocyte subsets with divergent and complementary functions

Abstract: Healing of myocardial infarction (MI) requires monocytes/macrophages. These mononuclear phagocytes likely degrade released macromolecules and aid in scavenging of dead cardiomyocytes, while mediating aspects of granulation tissue formation and remodeling. The mechanisms that orchestrate such divergent functions remain unknown. In view of the heightened appreciation of the heterogeneity of circulating monocytes, we investigated whether distinct monocyte subsets contribute in specific ways to myocardial ischemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

84
1,931
7
19

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 1,964 publications
(2,108 citation statements)
references
References 58 publications
84
1,931
7
19
Order By: Relevance
“…Mϕ have the intrinsic capacity to polarize between M1 (proinflammatory) and M2 (reparative) phenotypes; interestingly, we observed a strong shift toward an M2‐like Mϕ phenotype (Figure 9F and 9G). Taken together, these data suggest that salutary changes in Mϕ polarization from a “proinflammatory” toward a “healing” phenotype may contribute to cellular postconditioning, consistent with more‐extensive mechanistic studies in rats and in isolated macrophages 19, 20…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…Mϕ have the intrinsic capacity to polarize between M1 (proinflammatory) and M2 (reparative) phenotypes; interestingly, we observed a strong shift toward an M2‐like Mϕ phenotype (Figure 9F and 9G). Taken together, these data suggest that salutary changes in Mϕ polarization from a “proinflammatory” toward a “healing” phenotype may contribute to cellular postconditioning, consistent with more‐extensive mechanistic studies in rats and in isolated macrophages 19, 20…”
Section: Resultssupporting
confidence: 78%
“…Moreover, a subset of leukocytes (viz., neutrophils and monocytes) are associated with microvascular injury, LV remodeling, and function 34, 38. In addition, monocyte/macrophage heterogeneity post‐AMI is associated with the impairment of myocardial salvage and adverse LV remodeling 19. Here, we found that peripheral leukocyte counts are lower in CDC‐treated animals compared to placebo in the first 2 days postreperfusion.…”
Section: Discussionmentioning
confidence: 57%
“…To explain the above findings, we hypothesize that regional myocardial infarction induces an accumulation of monocytes/macrophages accompanied by an increase of cytokines that, in turn, can support angiogenesis and extracellular matrix synthesis by providing vascular endothelial growth factor, transforming growth factor‐β, and profibrotic transforming growth factor‐α after acute wound 30. Takamura et al reported that regulating the activation of proinflammatory macrophages post–myocardial infarction improves cardiac remodeling 31.…”
Section: Discussionmentioning
confidence: 99%
“…Takamura et al reported that regulating the activation of proinflammatory macrophages post–myocardial infarction improves cardiac remodeling 31. Indeed, Ly‐6C low macrophage has been shown to play a crucial role in the pathogenesis and progression of the healing myocardium 30. In addition, macrophage‐induced fibrosis and several cytokines could aggravate arrhythmogenic properties 32, 33.…”
Section: Discussionmentioning
confidence: 99%
“…Immediately after an ischemic insult, cardiac remodeling is initiated by a transient inflammatory response triggered through danger‐associated molecular (DAMP) patterns and cytokines released from injured cardiomyocytes, attracting immune cells into the infarcted area 5, 6. Once the wound is “cleared” and the inflammatory phase is repressed, fibroblasts are activated and recruited, followed by their proliferation and differentiation into myofibroblasts 7, 8. Myofibroblasts express and deposit large amounts of collagen to renew the extracellular matrix (ECM) compartment, therefore ensuring the integrity of the heart tissue 9, 10.…”
Section: Introductionmentioning
confidence: 99%